The Perceived Influence of Neurofibromatosis Type 1(NF1) on the Parents' Relationship - Lori Wiener; Sima Zadeh Bedoya; Archita Goyal; Mallorie Gordon; Natalie Deuitch; Brigitte Widemann (MDPI AG, 2023)
Neurofibromatosis type 1 (NF1) is a genetic condition affecting 1 in 3000 individuals. Having a child with a chronic illness can introduce both practical and emotional challenges to a parental relationship. This cross-sectional study was administered to 50 parents of children with NF1, diagnosed between the ages of 1-24. Each participant was provided a 50-item self-report survey to complete during an inpatient or outpatient visit. The survey gathered information on the participants' views of the spouse/partner relationship, coping mechanisms, and elements that supported emotional connections. While the majority of parental relationships were reported to remain strong, the mean relationship quality was perceived to have decreased compared to prior to the child's diagnosis. Compassionate and open communication, shared perspective, having time alone with their partner outside of medical situations, and dyadic coping were identified as strategies that could strengthen the relationship. The identified stressors to the parental relationship during the NF1 illness trajectory can inform interventions and help guide development of a couple's intervention. The National Cancer Institute, NIH Institutional Review Board approved this study (12-C-0206).